Interaction of environment and size on the drying shrinkage and creep of concrete. - Bargi, Nima. (University of Ottawa (Canada), 2002)
This report describes the significant observations from an ongoing, long duration experimental investigation into the joint interaction of environment, specimen size, duration of moist curing on shrinkage and creep. The different environments investigated are: (a) constant temperature conditions in a laboratory, uncontrolled relative humidity, (b) in a room of 50% relative humidity and constant temperature, (c) in water, and (d) outside exposure in the Ottawa area. The compressive strength of concrete subject to these environments was measured. A number of 89 mm diameter, 152 mm diameter, 254 mm diameters and 610 mm diameter cylinders were cast from a single batch and moist cured in their moulds for 3 days. All specimens were exposed to the chosen environment after moist curing 3∼4 days and typically loaded at 24 days. For the age of loading tests, 89 mm diameter specimens were loaded at concrete ages raging from 3 to 200 days, 152 mm diameter specimens were loaded at concrete age 24 days, 254 mm diameter specimens were loaded at concrete age 24 days (200 days for the outdoor environment specimens) and the 610 mm diameter specimens were loaded at concrete age 24 days in each of the chosen environments. The environments were inside (22°C, variable humidity), 22°C and 50% relative humidity, outside (uncontrolled temperature and humidity) and immersed in water. The compressive strengths of concretes stored in the laboratory and 50% RH environments had similar values but 50% RH shrinkage was slightly smaller. Although the compressive strength of specimens stored outside was slightly smaller than the identical ones stored in the lab in the first days, the ultimate compressive strength of concrete was much larger for specimens outside. The shrinkages of the specimens stored outside were 50% of the specimens stored in the 50% RH environment. The specimens stored in the 50% RH environment and the laboratory approached an ultimate limiting value ie the rate of increase in shrinkage after 1000 days was small. Increasing the duration of moist curing from 3 days to 25 days, reduced shrinkage but increasing the duration of moist curing from 25 days to 200 days had little effect. Storing specimens outside (specimens were cast December 1997) reduced shrinkage considerably. Whether the conclusion is valid for concrete cast in summer is not known. Creep is reduced by increasing specimen diameter, duration of moist curing and the age of loading. The creep of the immersed and sealed specimens was less than the specimens exposed to drying. The lower the relative humidity the larger the creep. Sealing decreased creep - sealing is more effective if it is done in the first few days after casting. Specimens stored outside had significantly smaller creeps. Lab and 50% RE had almost similar creeps but 50% RH was slightly smaller. The creep of the immersed specimens became asymptotic with time after some 1000 days of loading. However the creep of none of the specimens exposed to drying reached an ultimate value in the observation period. The elastic and creep Poisson's ratio of the concrete used was 0.18.
Keywords: Engineering, Civil.